Diversidade molecular e morfológica de Brycon (Characiformes, Characidae : Bryconinae) das porções superiores de drenagens amazônicas do Brasil Central - Arruda, Pábila Stephanie de Souza (2017)
Brycon Müller & Troschel, 1844 is composed of 44 species, widely distributed in the Neotropical freshwater basins. They are medium to large fish, migratory species, omnivores, important dispersers of forest seeds and riparian forests. They are used in sport fishing and feeding, representing one of the species of great importance in Brazilian fish farming. Although present ecological and commercial importance, it has observed a decrease in their populations as a result of the changes in their natural habitats derived from anthropic actions. These changes have led to the loss of biodiversity and many species have become extinct before being known. The aim of this study was to use an integrative approach based on molecular data (DNA barcode) and morphological, to identify how taxonomic units for Brycon in the middle and upper courses of the rivers basins Tapajós, Xingú, Araguaia and Madeira. were analyzed 201 sequences with a mean of 588 base pairs. Interspecific genetic distances were calculated by the Kimura-2- parameter nucleotide substitution model and ranged from 2.9% to 24.0%. Together with the analyzes of Neighbor-Joining, BIN and ABGD, allowing to assume the existence of at least twelve distinct lineages among the fish groups studied herein. The results showed that the species described as B. falcatus corresponds to more than one taxonomic unit, requiring further studies with more genes, along with morphological data to confirm the hypothesis of new species.